Developmental delay assessment in children < 5 years of age attended in the Pediatric Rehabilitation Service of a reference hospital in Peru - Roger De la Cerna-Luna; Daniel Fernandez-Guzman; Giancarlo Alvarado-Gamarra; Alvaro Taype-Rondan (Permanyer, 2023)
Background: Child development is a complex biological, psychological, and emotional process. Timely screening for developmental delay allows early interventions. Therefore, this study sought to assess the frequency and characteristics of developmental delay in children < 5 years of age who attended the Pediatric Rehabilitation Service of a referral hospital in Peru. Methods: We conducted a cross-sectional study. Information was collected from medical records of children < 5 years of age who attended between April and September 2022 at the Rebagliati Hospital's Pediatric Rehabilitation Service. The REBA-PED Child Developmental Assessment Profile was used for the developmental assessment, which allows to identify the degree of delay in each area (gross motor, fine motor, hearing and language, intelligence and learning, and personal-social) and the presence of warning signs. Results: Of 226 children who attended the service, 49.1% were between 3 and 5 years old, 57.1% were female, only 3.1% were referred for suspected developmental delay, and none had had a previous developmental assessment. Among the children evaluated, 12.4% had a simple developmental delay, 19.5% had a significant developmental delay, and 53.5% had a global developmental delay. In addition, 70.8% presented a warning sign of developmental delay. Hearing and language (86.8%) and intelligence and learning (83.5%) areas had a higher frequency of significant developmental delay. Conclusions: We found a high frequency of developmental delay in the children assessed, predominantly in hearing and language. Although all the children were referred, none had had a previous developmental assessment.